PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS GOOGLE SITES UNTUK MENINGKATKAN KEMAMPUAN LITERASI SAINS SISWA KELAS V SEKOLAH DASAR - Dia Safa Sahmura, Afa; Laila, Alfi; Putri Kusuma Ningdiah, Emelda; Pebrianti, Iis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop a valid, effective, and practical interactive learning media based on Google Sites to improve scientific literacy skills in fifth-grade elementary school students in Kediri. This study uses Research and Development (R&D) with the ADDIE model. The subjects were 49 fifth-grade students of SDN Bandar Lor 3 and 1. The research instruments consisted of material and media expert validation sheets, practicality response questionnaires by teachers and students, and pretest and posttest questions. The media validation results obtained a percentage of 94%, while the material validation obtained a percentage of 96.36%, both of which were categorized as very valid. The results of the teacher response questionnaire obtained a percentage of 92% with a very good category. The results of the student response questionnaire in the small-scale trial (SDN Bandar Lor 3) obtained an average of 88% with a good category, and in the large-scale trial (SDN Bandar Lor 1) obtained an average of 91% with a very good category, so the media was declared practical to use in learning. The N-Gain analysis showed an average of 0.81 in the small-scale test and 0.79 in the large-scale test, both of which are in the high category, indicating that the media is effective in improving students' scientific literacy skills. Based on these results, this learning media can be used by students in other schools to improve their scientific literacy skills and can serve as a reference for other similar research.